An analysis of funding liquidity risk in the South African banking system - Zonke, Khaya (Research of GSB, 2018)
Most emerging markets are faced with the predicament of a misalignment, or mismatch, of assets and liabilities in the banking sector where long-term assets are funded by short-term deposits. The South African (SA) banking sector also faces a challenge regarding the composition of the short-term deposits that fund these assets. The large and unstable wholesale funds dominate the funding side of local banks' balance sheets, particularly in the short-term bucket. The danger with wholesale funds arises when they are withdrawn unexpectedly, due to either perceived or realised risk. Due to their bulk, the wholesale funds have the potential to create a funding liquidity risk crisis in a bank. Most banks are unlikely to match these types of withdrawals, and will therefore have a forced asset fire sale to fund them. Retail funds do not face this danger, as it is highly unlikely, in normal market conditions, which many retail depositors would want to withdraw all their funds at the same time. Furthermore, retail funds are a cheaper source of funding compared to wholesale funds, thus making them a bank's preferred source of funding. In as much as they are a preferred source of funding, in the SA banking system retail deposits are very low compared to wholesale funding. This research study explores the funding liquidity risk and the predicament that exists in the SA banking industry by highlighting its main sources, and providing recommendations on how it can be addressed. This is achieved by testing the relationship between the ratio of retail funding to total bank funding (ROBF) and five explanatory variables, namely: household saving rates; retail deposit rates; corporate saving rates; wholesale deposit rates; and the Johannesburg Stock Exchange (JSE) All Share Index, with the aid of the multiple regression analysis method. The regression analysis was performed on data collected between 2002 and 2011. The research established that household saving rates and retail deposit rates were predictors that were statistically significant in explaining the movement in the ratio of retail funding to total funding.